Preliminary check-list of the marine, shelled gastropods (Mollusca) of Golfo Dulce, on the Pacific coast of Costa Rica - Hoisaeter, Tore (1998)
Based on partly worked up material from three brief collecting excursions to the peninsular shore of Golfo Dulce, 252 species of shelled gastropods, mostly prosobranchs and pyramidellids, have been identified. This being the first report on intertidal and shallow water gastropods from the gulf, the list may be taken as a preliminary check list of this fauna clement from Golfo Dulce. Only partly sorted material from two additional trips to the gulf contains at least 100 additional species not yet identified.